Gestão do clima para serviços em restaurantes - MATTOS, Carlos Eduardo de (2017)
The food and beverage sector (F&B) has been one of the businesses with the greatest potential to keep active in Brazil in 2017 and is one of the most promising for 2018. Within this sector, restaurants and other food services grow around 10% per year and employs around six million people in Brazil. In order to be profitable in the business, restaurants need to be oriented to the excellence of customer service and, to this end, the interaction between employees and customers appears as an important point in the perception of the quality of the consumer regarding the service received. In this sense, people management (HRM) seeks to know and understand the needs of employees in order to attract, motivate, develop and maintain them in the organization. In addition, employee attributes are also influenced by the organizational climate which, in turn, needs to be aligned with some strategic focus, such as customer service. So, a climate for services becomes favorable when employees realize that customer service is essential to the business and that they are rewarded for providing quality customer service. Thus, the objective of this work is to investigate how the HRM function can promote a favorable climate for services in a la carte, self-service and rotation restaurants in the city of Sorocaba. After conducting a multi-case study with these establishments and analyzing managers', employees' and clients' responses in four dimensions of services climate, the results showed that HRM practices promotes a positive service climate when seeking to influence and support staff offer a quality service to customers and reward them for it. This study contributed to the F&B area by showing that the managers use HRM practices and that these practices are helping the restaurants to achieve customer satisfaction in the customer service.